Deformation and Shear Strength Characteristics of Some Tropical Peat and Organic Soils - Kim Huat, Bujang (Universiti Putra Malaysia Press, 2006)
Peat and organic soils commonly occur as extremely soft, unconsolidated surficial deposits that are an integral part of the wetland systems. They may also occur as strata beneath other surficial deposits. These soils are problematic as they are very highly compressible and are of very low shear strength. In countries like Malaysia, peat and organic soils are found in abundance. Utilization of this marginal ground is required in increasing number of instances in the recent years. Hence suitable geotechnical design parameters and construction techniques needed to be found for this type of ground condition. This paper presents results of laboratory and field tests on the deformation and shear strength characteristics of tropical organic and peat soil. The soil samples were collected from several locations in Malaysia, namely from the states ofJohore, Perak, Sarawak and Selangor. These soils represented tropical peat and organic soils with organic content ranging from 50% to 95%.The soil compression index is found to increase with increase in the organic content and natural moisture content. While for case of undrained strength, the shear strength of tropical peat and organic soil is found to decrease with increase in the organic content and natural moisture content. The shear strength of the soil is also dependent on the degree of humification of the soil, with more fibrous soils having higher undrained strength.